2013
DOI: 10.1073/pnas.1219852110
|View full text |Cite
|
Sign up to set email alerts
|

Negative regulation of Toll-like receptor 4 signaling by IL-10–dependent microRNA-146b

Abstract: Toll-like receptors (TLRs) play key roles in detecting pathogens and initiating inflammatory responses that, subsequently, prime specific adaptive responses. Several mechanisms control TLR activity to avoid excessive inflammation and consequent immunopathology, including the anti-inflammatory cytokine IL-10. Recently, several TLR-responsive microRNAs (miRs) have also been proposed as potential regulators of this signaling pathway, but their functional role during the inflammatory response still is incompletely… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
234
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 245 publications
(252 citation statements)
references
References 34 publications
11
234
0
1
Order By: Relevance
“…The upregulation of miR-146 after LPS stimulation was also observed in monocytes derived from adult peripheral veins and from newborn CB (11). After LPS engagement, monocytes upregulate miR-146b which modulates the TLR4 signaling pathway by direct targeting of multiple elements, including TLR4, MyD88, IRAK-1, and TRAF6, via an IL-10-mediated STAT3-dependent loop (26). In addition, activation of the MAP kinase/EGR pathway by proinflammatory cytokines regulates the transcription of the miR-146, which can in turn repress the NF-κB, AP-1, and MAPK/EGR pathways.…”
Section: Lps-induced Mirnas In Tlr Signalsmentioning
confidence: 83%
“…The upregulation of miR-146 after LPS stimulation was also observed in monocytes derived from adult peripheral veins and from newborn CB (11). After LPS engagement, monocytes upregulate miR-146b which modulates the TLR4 signaling pathway by direct targeting of multiple elements, including TLR4, MyD88, IRAK-1, and TRAF6, via an IL-10-mediated STAT3-dependent loop (26). In addition, activation of the MAP kinase/EGR pathway by proinflammatory cytokines regulates the transcription of the miR-146, which can in turn repress the NF-κB, AP-1, and MAPK/EGR pathways.…”
Section: Lps-induced Mirnas In Tlr Signalsmentioning
confidence: 83%
“…Interestingly, miR146b-5p (P ϭ 00873), an LPS-responsive miRNA, showed statistically nonsignificant elevation at 180 dpi. Recent in vitro studies showed miR-146b-5p to be significantly upregulated following LPS treatment of THP monocytes; however, they showed delayed kinetics (39). This raised the question of whether translocated luminal bacteria and their products in the lamina propria (47) are triggering miR-146b-5p upregulation.…”
Section: Discussionmentioning
confidence: 99%
“…Alternatively, methods for manipulating anti-inflammatory cytokines such as IL-10 may yield some promise for treating drug-induced inflammation. IL-10 is a powerful suppressor of TLR-induced cytokine production (Curtale et al, 2013). In addition, IL-10 treatment has proven successful at treating animal models of neuropathic pain (Dengler et al, 2014;Kwilasz et al, 2015).…”
Section: Future Research Directions and Clinical Implicationsmentioning
confidence: 99%